The role of micronutrients on COVID-19 treatment for adults, children and elderly (Research, Society and Development, 2021)
Introduction: Coronaviruses have been shown to infect humans. Such viral types were the causing agents of the outbreaks of the Severe Acute Respiratory Syndrome. Specific malnutrition leads to deleterious effects on immunity. Thus, the treatment of these deficiencies, both in outpatients and inpatients with suspected SARS-CoV-2, could help the immune system to play its role in an optimal level of defense. Objective: This review aims to discuss the beneficial effects of treatments for specific deficiencies related to vitamins A, D, C, zinc, and selenium. Methods: This is a narrative review. The search included research in electronic databases and manual search for citations in LILACS and MEDLINE, developed between June 2020 and December 2020. Results and Discussion: The immune system undergoes changes throughout life and depends on an adequate supply of nutrients. Some micronutrients of the diet have very specific roles to develop and maintain an effective immune system. The most needed micronutrients to support immunocompetence are vitamins A, C, D, E, B2, B6, B12, folic acid and the minerals zinc, selenium, iron, magnesium, and copper. The diet is expected to supply an adequate amount of these nutrients. However, the daily intake of these necessary substances may be greater during  infection. This is particularly important in acute respiratory tract infections. Conclusion: This article demonstrates the importance of maintaining a balanced diet, with adequate intake of micronutrients, especially when it comes to the COVID-19 pandemic.